2022
DOI: 10.3389/fcell.2022.885537
|View full text |Cite
|
Sign up to set email alerts
|

The Oxidative Damage and Inflammation Mechanisms in GERD-Induced Barrett’s Esophagus

Abstract: Barrett’s esophagus is a major complication of gastro-esophageal reflux disease and an important precursor lesion for the development of Barrett’s metaplasia and esophageal adenocarcinoma. However, the cellular and molecular mechanisms of Barrett’s metaplasia remain unclear. Inflammation-associated oxidative DNA damage could contribute to Barrett’s esophagus. It has been demonstrated that poly(ADP-ribose) polymerases (PARPs)-associated with ADP-ribosylation plays an important role in DNA damage and inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The advanced glycation end products (AGE)/receptor of advanced glycation end products (RAGE) is an important pathway for abnormal glycosylation metabolism and is associated with aging-related diseases, including IPF ( Nedić et al, 2013 ; Machahua et al, 2016 ). Long-term reflux in GERD induces local inflammatory responses, and an incomplete ADP-ribosylation-dependent DNA damage response occurs ( Han and Zhang, 2022 ). A sensitive indicator of glycosylation - the lectins (UEA-1, DBA, HPA, and PNA) are also significantly reduced ( Neumann et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…The advanced glycation end products (AGE)/receptor of advanced glycation end products (RAGE) is an important pathway for abnormal glycosylation metabolism and is associated with aging-related diseases, including IPF ( Nedić et al, 2013 ; Machahua et al, 2016 ). Long-term reflux in GERD induces local inflammatory responses, and an incomplete ADP-ribosylation-dependent DNA damage response occurs ( Han and Zhang, 2022 ). A sensitive indicator of glycosylation - the lectins (UEA-1, DBA, HPA, and PNA) are also significantly reduced ( Neumann et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a few studies have explored the role of PARP1 in BE and EAC. Zhang et al have suggested that PARP1 hyperactivation in esophageal cells caused by GERD-induced oxidative stress and PARP1-mediated activation of NF-κB pathway may contribute the pathogenesis of BE [ 54 ]. Indeed, an up-regulation of PARP1 in BE patient tissues was observed by microarray compared with normal esophageal tissue [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…After adjusting for factors related to metabolic syndrome, the risk of RE was 2.029 times higher in NAFLD patients than in non-NAFLD patients. Several mechanisms have been proposed to explain how NAFLD may contribute to RE: (1) the abnormal movement of neurogenic oesophageal smooth muscle, resulting in decreased gastric acid clearance ability of the oesophagus and increased reflux attacks [ 28 , 29 ]; (2) the increased oxidative stress, leading to inflammation and ulceration of the oesophageal mucosa; (3) the reduced antioxidant function, reducing the repair ability of oesophageal mucosa while correspondingly increasing the severity of GERD [ 30 ]; (4) the pH-lowering effect of leptin released by adipose tissue of NAFLD patients on the oesophageal cavity, resulting in the damage to the oesophageal mucosa [ 31 ].…”
Section: Discussionmentioning
confidence: 99%